2003
DOI: 10.1016/s1146-609x(03)00007-9
|View full text |Cite
|
Sign up to set email alerts
|

Histochemistry and histology in planktonic ecophysiological processes determination in a temperate estuary (Mondego River estuary, Portugal)

Abstract: Zooplankton communities in temperate climates exhibit well documented seasonal variability. The reasons proposed to explain this kind of behaviour range from the effect of physical-chemical conditions (salinity, nutrients, temperature) growth rates, mortality, migration rates, food availability and predation. It is noticeable that the majority of the factors mentioned are external to the organisms, being environmental factors responsible for time dependent changes in zooplankton abundance. A question may arise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 40 publications
(59 reference statements)
1
4
0
Order By: Relevance
“…This is apparently related to individual nutritional status and breeding cycle (Lehtonen, 1996;Pastorinho et al, 2003). In the present study M. zeylanica have shown relatively high values of biochemical composition during the monsoon period.…”
Section: Discussionsupporting
confidence: 47%
“…This is apparently related to individual nutritional status and breeding cycle (Lehtonen, 1996;Pastorinho et al, 2003). In the present study M. zeylanica have shown relatively high values of biochemical composition during the monsoon period.…”
Section: Discussionsupporting
confidence: 47%
“…Yousefian and Kideys (2003) found that the proteins decreased by 13.4% after 5 days of fasting, whereas the lipids decreased by 46.3%, where as, low sugars decreased by 24.5%. As for lipid changes, it is related to metabolism and reproductive strategy (Pastorinho, et al 2003).…”
Section: Discussionmentioning
confidence: 99%
“…This is apparently related to the individual's nutritional status and breeding cycle (Pastorinho et al, 2003). This is apparently related to the individual's nutritional status and breeding cycle (Pastorinho et al, 2003).…”
Section: Biochemical Compositionmentioning
confidence: 99%